Issuance Expenses and Common Stock Offerings for Over-the-Counter Firms - Robert M. Hull; Richard Fortin (Journal of Small Business Finance, 1993)
This study explores the role of issuance expenses in explaining the fall in stock value for OTC stock offerings that raise cash for debt reduction purposes. It estimates that over half of the sample's -2.79% two-day fall in stock value can be accounted for by issuance expenses when using a lower bound measure of issuance expenses. This estimate contrasts with the one-fifth estimate suggested by NYSE/AMEX studies that examine stock offerings that raise cash primarily for non-debt reduction purposes. The influence of issuance expenses is shown to be substantially greater when combination offerings are deleted, an upper bound measure of issuance expenses is employed, or the sample is restricted to those offerings with the greatest issuance expenses per outstanding share.
Keywords: G12; G32; 650; Issuance Expenses; Issuance Fees; Stock Offerings; Over-the-Counter; OTC